Resistive vibration exercise retards bone loss in weight-bearing skeletons during 60 days bed rest - Wang, H.; Wan, Y.; Tam, K.-F.; Ling, S.; Bai, Y.; Deng, Y.; Liu, Y.; Zhang, H.; Cheung, W.-H.; Qin, L.; Cheng, J. C.-Y.; Leung, K.-S.; et al. (Osteoporosis international, 2012)
Summary Countermeasures are desirable to retard bone loss during long-term space flight. We evaluated the effect of an intervention protocol on bed rest-induced bone loss. Introduction We developed a resistive vibration exercise (RVE) platform to test if an intervention RVE protocol would be effective to protect bed rest-induced bone loss. Methods Fourteen male subjects were assigned randomly to either the RVE group ( n = 7) that performed daily supervised resistive vibration exercise or to the no any exercise control (CON) group ( n = 7). Both dual-energy X-ray absorptiometry and peripheral quantitative computed tomography were used to monitor changes in bone mineral density. Results RVE significantly prevented bone loss at multiple skeletal sites, including calcaneus, distal tibia, hip, and lumbar spine (L2–L4). The ratio of urinary calcium and creatinine was found higher after starting bed rest in CON group while no significant changes were observed in RVE group. No significant temporal change was found for osteocalcin-N during and after bed rest in CON group. However, a significant increase was shown after bed rest in RVE group. In both groups, the urinary concentration of bone resorption markers, such as C-telopeptide of type I collagen (CTX-I) and deoxypyridinoline (DPD), were significantly elevated after bed rest. In the CON group, no significant temporal effect was found for hydroxyproline (HOP), CTX-I, and DPD during bed rest and the serum concentration of HOP and TGF-β significantly increased about 52.04% and 24.03%, respectively only after bed rest. However, all these markers tended to decrease in the RVE group. Conclusions Our results might imply that the intervention of RVE retarded bone loss induced by simulated microgravity in humans that was mainly attributed to its anabolic effects.